2016
DOI: 10.1371/journal.pone.0164590
|View full text |Cite
|
Sign up to set email alerts
|

Mining, Validation, and Clinical Significance of Colorectal Cancer (CRC)-Associated lncRNAs

Abstract: BackgroundColorectal cancer (CRC) is one of the deadliest tumours, but its pathogenesis remains unclear. The involvement of differentially expressed long non-coding RNAs (lncRNAs) in CRC tumorigenesis makes them suitable tumour biomarkers.Methods/FindingsHere, we screened 150 cases of CRC and 85 cases of paracancerous tissues in the GEO database for differentially expressed lncRNAs. The levels of lncRNA candidates in 84 CRC and paracancerous tissue samples were validated by qRT-PCR and their clinical significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…TCGA and GEO are international public repositories that contain a large number of genomic datasets, and several genes that have diagnostic value in colorectal cancer have been found using these datasets [ [27] , [28] , [29] , [30] ]. Using bioinformatics analysis, we found that SETD7 , but not FGA and MUC5AC , is expressed at significantly higher levels in CRC than in normal colorectal mucosa tissue.…”
Section: Discussionmentioning
confidence: 99%
“…TCGA and GEO are international public repositories that contain a large number of genomic datasets, and several genes that have diagnostic value in colorectal cancer have been found using these datasets [ [27] , [28] , [29] , [30] ]. Using bioinformatics analysis, we found that SETD7 , but not FGA and MUC5AC , is expressed at significantly higher levels in CRC than in normal colorectal mucosa tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the lncRNAs involved in the development, diagnosis, and prognosis of colon cancer. For instance, Sun et al (2016) found a lncRNA (AK098081) that can serve as an independent risk factor for colon cancer by analysis of GEO datasets (150 cases). Moreover, Li et al (2017) identified eight novel lncRNAs associated with the prognosis of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The rising incidence and high metastasis of CRC has become an urgent problem in diagnosis and treatment (Sun et al, ), but unfortunately, lack of the information about the molecular mechanism in CRC, has brought a considerable burden on CRC treatment (Zhang, Yang, & Chen, ). Thus, more investigation of biological function or molecular mechanism should be carried out.…”
Section: Discussionmentioning
confidence: 99%